Membrane microdomains modulate oligomeric ABCA1 function: impact on apoAI-mediated lipid removal and phosphatidylcholine biosynthesis - Iatan, Iulia (The American Society for Biochemistry and Molecular Biology, 2011)
Recent studies have identified an ABCA1-dependent, phosphatidylcholine-rich microdomain, called the “high-capacity binding site” (HCBS), that binds apoA-I and plays a pivotal role in apoA-I lipidation. Here, using sucrose gradient fractionation, we obtained evidence that both ABCA1 and [(125)I]apoA-I associated with the HCBS were found localized to nonraft microdomains. Interestingly, phosphatidylcholine (PtdCho) was selectively removed from nonraft domains by apoA-I, whereas sphingomyelin and cholesterol were desorbed from both detergent-resistant membranes and nonraft domains. The modulatory role of cholesterol on apoA-I binding to ABCA1/HCBS was also examined. Loading cells with cholesterol resulted in a drastic reduction in apoA-I binding. Conversely, depletion of membrane cholesterol by methyl-β-cyclodextrin treatment resulted in a significant increase in apoA-I binding. Finally, we obtained evidence that apoA-I interaction with ABCA1 promoted the activation and gene expression of key enzymes in the PtdCho biosynthesis pathway. Taken together, these results provide strong evidence that the partitioning of ABCA1/HCBS to nonraft domains plays a pivotal role in the selective desorption of PtdCho molecules by apoA-I, allowing an optimal environment for cholesterol release and regeneration of the PtdCho-containing HCBS. This process may have important implications in preventing and treating atherosclerotic cardiovascular disease.